2016
DOI: 10.1007/s12288-016-0647-1
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly 1.6 mg/m2 Bortezomib BCD Regimen in Elderly Patients with Newly Diagnosed Multiple Myeloma Who are Unfit for Standard Dose Chemotherapy

Abstract: Bortezomib has shown anti-myeloma effects in combination with alkylating agents, but clinical benefits can be limited by neurotoxicity. There is less information on the efficacy and tolerability of once-weekly 1.6 mg/m 2 bortezomib combined with cyclophosphamide and dexamethasone (BCD) regimen in elderly patients with newly diagnosed multiple myeloma who are unfit for standard dose chemotherapy. Here, we report our experience of weekly 1.6 mg/m 2 intravenous bortezomib in this group of patients. Between March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In the context of the VCD regimen, weekly delivery of bortezomib has been reported in transplant-eligible populations, 21 , 22 , 23 , 24 but there have only been a few small retrospective reports of a weekly VCD regimen for the initial treatment of older patients. 25 , 26 The schedule of VCD in our trial, using 4-weekly bortezomib doses in a 5-week cycle, proved highly tolerable despite the older and frail population. Approximately 80% of patients in the VCDD arm completed the planned 9 cycles of induction, with an all-grade peripheral neuropathy rate of 28% and no grade 3 or 4 events.…”
Section: Discussionmentioning
confidence: 82%
“…In the context of the VCD regimen, weekly delivery of bortezomib has been reported in transplant-eligible populations, 21 , 22 , 23 , 24 but there have only been a few small retrospective reports of a weekly VCD regimen for the initial treatment of older patients. 25 , 26 The schedule of VCD in our trial, using 4-weekly bortezomib doses in a 5-week cycle, proved highly tolerable despite the older and frail population. Approximately 80% of patients in the VCDD arm completed the planned 9 cycles of induction, with an all-grade peripheral neuropathy rate of 28% and no grade 3 or 4 events.…”
Section: Discussionmentioning
confidence: 82%
“…[33] Hence, the aim of alternative bortezomib regimens is to reduce adverse reactions while ensuring efficacy. [19,34] So far, the studies suggest that the efficacy of the bortezomib once weekly regimen is relatively good and with low toxicity in patients with MM, [22,2527] but data are still lacking in various populations.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,21,22] Although the standard bortezomib regimen shows more significant effects than the traditional chemotherapy regimens, its adverse reactions including thrombocytopenia, leukopenia, severe peripheral neuropathy (PN), gastrointestinal reactions, herpes zoster, and various infections [23] often lead to the reduction of the dose and even to the termination of treatment, affecting the efficacy and prognosis. [24] Therefore, alternative less toxic regimens are being sought, such as changing from twice weekly to once weekly [22,2527] or from the traditional intravenous administration to subcutaneous injection. [28,29] So far, the studies suggest that the efficacy of the bortezomib once weekly regimen was relatively good and with low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of novel therapeutics including immunomodulatory agents (thalidomide, lenalidomide) and proteasome inhibitors (bortezomib), the prognosis of patients with MM has significantly improved. Recent studies have confirmed the significance of deep response particularly complete response (CR) or very good partial response (VGPR) to induction therapy for patients with newly diagnosed MM (4)(5)(6).…”
Section: Introductionmentioning
confidence: 97%